Release of Envelope Glycoprotein from Rabies Virions by a Nonionic Detergent - György, Emese (1971)
Treatment of rabies virus with the nonionic detergent Nonidet P-40 resulted in solubilization of viral lipids and in a preferential release of the envelope glycoprotein. The other viral proteins and the viral ribonucleic acid remained associated in “core” particles sedimenting at a rate similar to that of intact virions. After fractionation of treated virus by velocity centrifugation in a sucrose density gradient, the amount of residual glycoprotein recovered in the “core” particle fraction and the extent of contamination of the glycoprotein fraction by other viral components were dependent on the ratio of detergent to viral protein used.